Prevalence and risk factors associated with prehypertension in Shunde District, southern China - Yuli Huang; Yunzhao Hu; Xiaoyan Cai; Wenke Qiu; Changhua Liu; Dingji Zhu; Jinghai Hua; Yanxian Wu; Dingli Xu (BMJ Open)
Objective To explore the prevalence and combined cardiovascular risk factors of prehypertension in southern China.Design A retrospective study; the logistic regression model was used to find the risk factors of prehypertension.Setting The study was conducted in Shunde District, southern China, using the community-based health check-up information.Participants Participants aged ≥35 years with complete health check-up information data between January 2011 and December 2013 were enrolled and divided into hypertension, prehypertension and optimal blood pressure (BP) groups. Prehypertension was further divided into low-range (BP 120–129/80–84 mm Hg) and high-range (BP 130–139/85–89 mm Hg) subgroups.Outcome measures The prevalence of prehypertension and the combined cardiovascular risk factors within the prehypertensive subgroups.Results Of the 5362 initially reviewed cases (aged ≥35 years), 651 were excluded because of missing data. The proportions of optimal BP, prehypertension and hypertension were 39.1%, 38.6% and 22.3%, respectively. The average age, proportion of male sex, overweight, impaired fasting glucose (IFG), dyslipidaemia and hyperuricaemia were significantly higher in the prehypertension group than in the optimal BP group (all p <0.05). Compared with low-range prehypertension, the proportions of overweight, dyslipidaemia and IFG were higher in the high-range prehypertension group (all p<0.05). Multivariate logistic regression analysis showed that overweight (OR=2.84, 95% CI 1.55 to 5.20), male sex (OR=2.19, 95% CI 1.39 to 3.45), age (per 10 years, OR=1.21, 95% CI 1.02 to 1.44, p=0.03) and hyperuricaemia (OR=1.70, 95% CI 1.14 to 2.54) were independent risk factors of prehypertension.Conclusions Prehypertension is highly prevalent in southern China. Prehypertensive individuals presented with many other cardiovascular risk factors. There was heterogeneity of combined risk factors within the prehypertensive subgroups.